Patterns of Mother, Father, and Peer Attachment Quality as Moderators of Child Maltreatment Risk for Depression and PTSD Symptoms in Adolescent Females - Russotti, Justin (Journal of interpersonal violence, 2023)
Child maltreatment (CM) is a robust risk factor for adolescent depressive and post-traumatic stress disorder (PTSD) symptoms. Quality attachment relationships have been posited as a protective factor but findings are equivocal and studies have not adequately considered the complex network of interpersonal relationships that adolescents rely on. The current study applied a person-centered approach to (a) identify subgroups of adolescent females characterized by distinct patterns of attachment quality with peers, fathers, and mothers and (b) determine if the effect of maltreatment on depressive and PTSD symptoms varied as a function of distinct patterns of attachment quality. Data came from a prospective, longitudinal cohort study of 464 racially diverse and adolescent females designed to examine the developmental sequelae of substantiated CM (260 maltreated and 204 demographically matched, nonmaltreated comparisons). Latent profile analysis (LPA) revealed four profiles of attachment characterized by: (a) above-average attachment quality across all three relationships (N = 207, 44.6%); (b) below-average quality with father and friends and above-average quality with mothers (N = 128, 27.6%); (c) below-average quality across all three relationships (N = 106, 22.9%); and (d) very low-(−1 SD) quality with mothers and above-average quality with fathers and friends (N = 23, 5.0%). Moderation models revealed that cumulative maltreatment exposure resulted in greater adolescent depressive symptoms only for those with a profile of attachment consisting of very low-quality maternal attachment and high-quality father and friend attachments. Profiles did not significantly moderate the effect of maltreatment on PTSD symptoms. Results identify subgroups of maltreatment survivors most vulnerable to the development of depression in adolescence. Such groups should be targets for the provision of finite clinical resources with clinical interventions that seek to promote healthy maternal attachment relationships to mitigate the impact of maltreatment on depression.